Effect of Cash Management on the Retail Industry's Financial Performance - Ariel G. Cabildo; Renalito D. Marcelo; Emmanuel John V. Angeles; Richard E. Olipas; Joefil C. Jocson (International Journal of Engineering and Management Research, 2022)
For all firms to improve their financial management and ensure their financial sustainability, cash management is essential. Each organization needs to use sophisticated cash management procedures in order to achieve its goals. The retail sector is also one of the most important for the growth of the Philippine economy and the creation of jobs, thus this study looked empirically at the impact of cash management on the financial performance of the sector over a five-year period, from 2016 to 2021. To determine whether cash management has had an effect on these five (5) significant retails organizations' financial performance, the study looks at their financial statements. The data was gathered from each retail company's financial statement and website on the Philippine Stock Exchange Edge website. The study used the cash management ratio, or Cash Ratio (CR), as the independent variable, and the financial performance ratios, or Return on Assets (ROA), Return on Equity (ROE), and Net Profit Ratio, as the dependent variables. In order to ascertain the correlations between different aspects of cash management and financial success, numerous regression and correlation analysis on the data were performed. The research found that the selected five (5) retail enterprises' financial performance was positively but marginally impacted by the Cash Ratio. The report thus advises that these key firms in the Philippine retail sector execute their cash management effectively in a way that enhances financial success.